What is moral disengagement? / Intan Marzita Saidon and Nadzri Ab Ghani - Saidon, Intan Marzita; Ab Ghani, Nadzri (Faculty of Accountancy, UiTM Kedah, 2018)
The notion of moral disengagement was developed as an extension of the social cognitive theory. This theory helps to explain why certain people are able to engage in inhumane conduct without apparent distress (Bandura, 2002). The theory proposes eight interrelated moral disengagement mechanisms.